What Matters the Most? Exploratory Analysis of Environmental and Situational Variables Influencing Performance of Students During COVID-19 Pandemic - Jamalova, Maral; Bálint, Csaba (International Journal of Emerging Technologies in Learning (iJET), 2023)
This study examines the impact of gender and age differences on the performance of students from different Hungarian universities and colleges in online learning during the third wave of COVID-19. The survey responses were assessed using Partial Least Squares estimation technique. The research model attempts to understand the influence of environmental and situational variables (i.e., compatibility, accessibility, perception of online self-efficacy, mobility) on performance and satisfaction with online education. Apart from mobility, other indicators have significant impact on respondents’ performance. However, moderating effect of age and gender almost do not influence the performance of surveyed Hungarian students. The results demonstrate that gender impacts the compatibility → performance pathway. The age of respondents has no effect on relationships between environmental and situational variables and performance.